PROTOTIP GROUND ENHANCEMENT MATERIAL (GEM) BERBAHAN BAKU Na-BENTONIT KARANGNUNGGAL - TASIKMALAYA SEBAGAI BAHAN SUBSTITUSI GEM IMPOR - Eko Tri Sumarnadi Agustinus; Happy Sembiring; Lina Nur Listiyowati (JURNAL RISET GEOLOGI DAN PERTAMBANGAN, 2010)
ABSTRACT GEM is one of the composite material which is used as backfill to protect the electronic equipments, communication network and to stem the voltage of the electrical power problem. GEM has been commonly used in Indonesia, but it is still imported. Therefore it is important to look for substitution minerals. The main compositions of GEM are silica (Si), Aluminium (Al) and carbon (C ). Therefore, this research focus on the aluminofilosilicate minerals (bentonite, from Karangnunggal, Tasikmalaya), and charcoal. Laboratory experimentations include characterizations of raw materials, mineral engineering, and developing formulation and prototype of GEM. The result of this characterizations show that Na-bentonite is the most potential material for GEM raw materials (resistivity 514 Ohm cm). Mineral engineering is used to obtain the GEM formula and prototype in powder form with composition of 70% Na-bentonite, 24% charcoal, and 6% NaCl. However, practically it is necessary to add 5% water glass and 36% moisture content into the powder in order to obtain the resistivity of 16.4 Ohm cm. This study results in GEM which is qualified for the grounding materials standard (resistivity < 25 Ohm cm).